2005
DOI: 10.2320/matertrans.46.384
|View full text |Cite
|
Sign up to set email alerts
|

Current Status of Fusion Reactor Structural Materials R&D

Akira Kohyama

Abstract: Japanese activities on fusion structural materials R&D have been well organized under the coordination of university programs and JAERI/NIMS programs more than two decades. Where, two categories of structural materials have been studied, those are; reduced activation ferritic/martensitic steels (RAFs) as reference material and vanadium alloys and SiC/SiC composite materials as advanced materials. The R&D histories of these candidate materials and the present status in Japan are reviewed with the brief explanat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Much stronger anisotropy in strength has been noted for ARB processed material with the specimen tested along 90• possesses the highest yield strength. [36][37][38][39][40][41] Strength of the specimens tested along 0• or 45• is almost the same. The ductility, on the other hand, varies with testing direction for both starting and ARB processed material.…”
Section: Mechanical Characterizationmentioning
confidence: 94%
See 1 more Smart Citation
“…Much stronger anisotropy in strength has been noted for ARB processed material with the specimen tested along 90• possesses the highest yield strength. [36][37][38][39][40][41] Strength of the specimens tested along 0• or 45• is almost the same. The ductility, on the other hand, varies with testing direction for both starting and ARB processed material.…”
Section: Mechanical Characterizationmentioning
confidence: 94%
“…This can be attributed to the fine grain size in the ARB processed material. It has been reported that PLC effect in AA5088 alloy weakens on reducing the grain size from 61 to 35 m and disappears altogether on further reduction to 13 m [37]. Instabilities in the post necking region for ARB processed material indicate continuous local fracture of layers before the final fracture could initiate along the last interface.…”
Section: Mechanical Behavior Of Arb Processed Materialsmentioning
confidence: 99%
“…The fusion structural materials should have good mechanical properties at high temperatures, good corrosion resistance with the coolant, be able to accommodate high heat loads, and have low levels of induced radioactivity. Vanadium alloys are under consideration for use in fusion energy systems as structural materials because they offer significant advantages over other iron based alloys in several of the areas mentioned above [ 71 , 72 ]. Extensive research in the past two decades has lead to a basic understanding of the physical, mechanical and metallurgical aspects of vanadium alloys including the effects of radiation.…”
Section: Perspectives On Friction Stir Processingmentioning
confidence: 99%
“…The NITE SiC/SiC composites were fabricated at Ube Co. Ltd using b-SiC nano-powder (Marketech International Inc., USA). This NITE SiC/SiC composite grade is named Pilot grade-2 [8]. The particle size of b-SiC nano-powder was below 30 nm.…”
Section: Methodsmentioning
confidence: 99%